Implementasi Aplikasi Berbasis Web untuk Pelaporan Kegiatan dan Proyek Pembangunan Desa Menggunakan Metodologi Agile (INTEK : Jurnal Informatika dan Teknologi Informasi, 2025)
Reporting on village activities and development projects plays a crucial role in ensuring that each project runs effectively and in accordance with established plans. Until now, the reporting process has been carried out manually through the WhatsApp application and by processing data using Excel. This approach is considered inefficient, prone to errors, and slows down the eval_uation and decision-making process, thereby hindering the overall optimization of village development. This study aims to develop a web-based information system for reporting village activities and development projects in order to enhance the effectiveness and efficiency of the reporting process. The development model employed is Agile, with stages including software requirements analysis, system design, program coding, and system maintenance. The system is equipped with features such as real-time monitoring, development report management, activity photo documentation, village event data management, user authentication, and report approval functionality. The implementation results show that the system is capable of simplifying the reporting process, accelerating data processing, improving recording accuracy, minimizing the risk of manual input errors, and enabling real-time project monitoring. The existence of this system makes the workflow of village staff more efficient and productive, supports information transparency, and accelerates data-driven decision-making, ultimately contributing to the advancement of village development.